Elevated liver enzymes as a marker of dengue disease severity and its prognostic implications - Mishra, Abhishek; Shakya, Yogendra Man; Shrestha, Tirtha Man; KC, Arjun; Mahat, Pradeep; Shrestha, Santosh Kumar; KC, Bipana; Neupane, Jeevan (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Dengue, the most important arthropod-borne disease, is transmitted to humans by mosquitos of the Aedes family. Liver dysfunction in dengue varies from mild injury with elevation of transaminases to severe hepatocyte injury. The aim of our study was to correlate the severity of the disease with the extent of hepatic dysfunction. Method: A prospective observational study was conducted at a tertiary care center in adults presenting to the emergency department and/or OPD diagnosed with dengue fever from 24 Nov 2022 to 25 Nov 2023. Result: Among 151 patients included in the study, males predominated - 84 (55.6%). The most common presentation was fever- in 115 (76.2%). There were 50 (33.11%) patients with Dengue without warning signs and 97 (64.23%) with warning signs. Only 4 (2.64%) were classified as severe Dengue. NS1 antigen was positive in about 141 (93.4%), Dengue IgM in 12 (7.9%), and IgG in 4 (2.6%) of the patients. Bleeding manifestations were present in about 13 (8.6%). Three required blood transfusions. There was no mortality. On multivariable OR analysis, in the severe Dengue group, both AST and ALT showed statistical significance in predicting the severity of Dengue fever. Conclusion: Elevations in hepatic enzymes—ALT and AST—demonstrated a notable level of accuracy in determining the severity of Dengue fever and in prognosticating it. Plasma AST and ALT levels were higher in individuals who developed severe Dengue, suggesting that elevations in hepatic enzymes could be used as an early marker of the severity of dengue.